UJI POTENSI EKSTRAK DAUN PETAI CINA (LEUCAENA LEUCOCEPHALA) SEBAGAI ANTI BAKTERI STAPHYLOCOCCUS EPIDERMIDIS DAN EFEK PENYEMBUHAN LUKA EKSISI PADA MENCIT BALB/C - Hanafi, Raden Wahid; Widiani, Nenny; Khikmatunnaiz, Miarti (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
The research is aimed at finding out the effectiveness of the extract of petai cina leavesagainst Staphylococcus epidermidis bacteria and the effect on curing the excision injury inBalb/C rats when compared to those widely sold in the society.The research method included extracting petai cina leaves by using maceration method.The sensitivity of the extract to Staphylococcus epidermidis bacteria and to the excision injuryin rat was then tested by using other types of medicine containing 10 % of providone iodinewidely sold.The research result showed that the extract of petai cina leaves could obstruct the growthof Staphylococcus epidermidis bacteria with the obstruction level as much as 14 mm. Thetest on the excession injury on rats also showed the same result as other types of medicinesold in drugstores.Keyword: petai cina, Staphylococcus epidermidis, rat Balb/C